2019
DOI: 10.1002/jcp.28532
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression, protein profiling, and chemotactic activity of infrapatellar fat pad mesenchymal stem cells in pathologies of the knee joint

Abstract: The infrapatellar fat pad (IPFP) is a periarticular adipose knee tissue. This tissue contains a large number of mesenchymal stem cells (MSCs). In the present work, we wanted to study the IPFP MSCs and their relationship and differences in two groups, anterior cruciate ligament (ACL) ruptures knees and ostheoarthrosis (OA). The IPFP of 42 patients with OA or ACL rupture were analyzed. Isolation, primary culture, and a genetic and proteomic study of MSCs from IPFP were performed. Gene expression of IL‐6, tumor n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…17,25 A higher gene expression of IL-6 was found in mesenchymal stem cells from the fad pad of OA patients compared with a control group of patients with an ACL rupture. 41 Favero et al 25 detected increased IL-6 protein levels in OA IPFPs compared with control IPFPs from cadavers with no signs of knee OA. We found no differences in the staining intensity scores of IL-1β and IL-6 between OA and control samples from the young with a rupture of the ACL.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…17,25 A higher gene expression of IL-6 was found in mesenchymal stem cells from the fad pad of OA patients compared with a control group of patients with an ACL rupture. 41 Favero et al 25 detected increased IL-6 protein levels in OA IPFPs compared with control IPFPs from cadavers with no signs of knee OA. We found no differences in the staining intensity scores of IL-1β and IL-6 between OA and control samples from the young with a rupture of the ACL.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies have shown that also the IPFP secretes proinflammatory cytokines and may modulate the inflammatory processes contributing to the pathomechanism of knee OA . A higher gene expression of IL‐6 was found in mesenchymal stem cells from the fad pad of OA patients compared with a control group of patients with an ACL rupture . Favero et al detected increased IL‐6 protein levels in OA IPFPs compared with control IPFPs from cadavers with no signs of knee OA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All 12 included articles were controlled single-institution studies (Table 2). Of the 12 isolated studies, 11 were retrospective [23][24][25][26][27][28][29][30][31][32][33] and one was a prospective cohort study [34]. There was a total of 228 patient IFPs assessed in the 12 studies.…”
Section: Included Studiesmentioning
confidence: 99%
“…The patient ages ranged between 17 and 89. From the six studies indicating gender [23][24][25]27,31,34], 77 (62%) patients were female and 48 (38%) were male.…”
Section: Included Studiesmentioning
confidence: 99%